Counter-imaging Australia’s agricultural landscapes for digital sustainability communication - Joshua Zeunert; Alys Daroy (Sustainability: Science, Practice, & Policy, 2025)
Industrial agriculture exerts significant ecological pressures, leading to biodiversity loss, ecosystem degradation, and biocapacity drawdown. Environmental impacts are often concealed due to physical (remoteness from city centers) and conceptual distancing (romanticized portrayals through advertising), hindering agricultural transparency. This article documents a creative digital methodology developed to communicate the scale and environmental impacts of industrial agriculture and to link consumers’ food choices with their sources. Research centers on the creation of “Food Landscapes Australia,” an interactive digital dissensus archive designed to expose the environmental consequences of the country’s agri-food system. The methodology integrates systematic spatial-statistical analysis, typological classification, continental-scale field research, a visual method for drone-image capture, and the immersive online dissemination archive. The archive includes 881 curated cinematographic drone videos, distilled from over 10,000 images captured across 38,000 kilometers of field research, systematically framing Australia’s agricultural activities and environmental impacts. Findings reveal the potential of these digital methodologies to produce high-resolution, incisive visual evidence that challenges dominant agri-food sustainability narratives, exposing often-concealed practices. The methodology, therefore, offers a contextually adaptable approach for sustainability researchers, educators, and policymakers to enhance environmental communication of agricultural impacts. Outcomes foster public awareness and critical reflection on sustainability issues and, by bridging the gap between production landscapes and food consumers, demonstrate the potential of digital tools for encouraging informed discourse and decision-making around sustainable food systems.